Transformation of the Education Curriculum in Indonesia during the Dutch East Indies Rule: A Historical and Conceptual Review - Jesika Indah Sari Purba; Perangin-angin, Desta Riani Br; Sembiring, Santa Hoky Br; Sihotang, Marnita; Zalukhu, Desveromika; Sinaga, Rosmaida (ETDC: Indonesian Journal of Research and Educational Review, 2025)
This study investigates the enduring impact of colonial legacies on Indonesia's national education system. The main objective is to analyze how structures, language policies, and bureaucratic frameworks inherited from the Dutch colonial era continue to shape educational access, quality, and equity today. Using a qualitative research approach, the study reviews secondary data, including academic articles and policy documents, combined with thematic analysis to identify key patterns and influences. The findings reveal that the dual-track curriculum system, separating academic and vocational education, perpetuates social segmentation, particularly disadvantaging students from lower socioeconomic backgrounds. Furthermore, the colonial use of Dutch as the primary language of instruction has created a longstanding preference for foreign languages, such as English, in formal education, which exacerbates learning inequalities between urban and rural areas. The study also highlights how the rigid, hierarchical educational bureaucracy inherited from the colonial period limits innovation and local adaptation in schools. Overall, the research concludes that addressing these challenges requires more than superficial curriculum revisions; it calls for deep systemic reforms that prioritize inclusivity, local relevance, and greater flexibility in educational management. By transforming these inherited structures, Indonesia can move toward a more equitable and high-quality national education system that better serves its diverse population.